2019
DOI: 10.1161/jaha.119.013228
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome‐Wide Association Study for All‐Cause Mortality in a Cardiovascular Cohort Identifies Differential Methylation in Castor Zinc Finger 1 ( CASZ1 )

Abstract: Background DNA methylation is implicated in many chronic diseases and may contribute to mortality. Therefore, we conducted an epigenome‐wide association study (EWAS) for all‐cause mortality with whole‐transcriptome data in a cardiovascular cohort (CATHGEN [Catheterization Genetics]).Methods and ResultsCases were participants with mortality≥7 days postcatheterization whereas controls were alive with≥2 years of follow‐up. The Illumina Human Methylation 450K and EPIC arrays (Illumina, San Diego, CA) were used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…ALPPL2 is another consistently replicated smokingmethylation locus, where the protein is a membranebinding glycosylated enzyme and is considered to be a highly specific tumour cell surface antigen [51]. DNA methylation of ALPPL2 has also been associated with all-cause mortality [52]. Furthermore, a recent EWAS of CHD identified signals in AHRR (cg05575921) and near ALPPL2 (cg21566642) to be associated with retrospective CHD with validation in independent iCHD samples [53].…”
Section: The Emerging Blood-based Dna Methylation Signatures Of Ichdmentioning
confidence: 99%
“…ALPPL2 is another consistently replicated smokingmethylation locus, where the protein is a membranebinding glycosylated enzyme and is considered to be a highly specific tumour cell surface antigen [51]. DNA methylation of ALPPL2 has also been associated with all-cause mortality [52]. Furthermore, a recent EWAS of CHD identified signals in AHRR (cg05575921) and near ALPPL2 (cg21566642) to be associated with retrospective CHD with validation in independent iCHD samples [53].…”
Section: The Emerging Blood-based Dna Methylation Signatures Of Ichdmentioning
confidence: 99%
“…CASZ1 expression is essential for cardiomyocyte cell-cycle progression in the cardiovascular system [24]. A research has shown that CASZ1 gene was associated with BP [25], and methylation in CASZ1 may be associated with cardiovascular patients in regulating mortality [26]. It was widely known that BP is signi cantly associated with weight gain [18].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have set less threshold for |log FC| with the assumption that fold change depends on many factors like type of study performed, stage of disease at which sample was collected, methods used to perform the study, etc. Hence we assumed that the fold change in methylation profiling study might be far lower than that in the expression profiling study ( Maag et al, 2017 ; Raman et al, 2018 ; Abdulrahim et al, 2019 ; He et al, 2019 ; Yang et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%